2008
DOI: 10.1007/s10661-008-0624-8
|View full text |Cite
|
Sign up to set email alerts
|

Metal concentrations in water, sediment, and fish from sewage-fed aquaculture ponds of Kolkata, India

Abstract: The concentrations of lead, cadmium, chromium, copper, and zinc were investigated in the sewage-fed pond water, sediment, and the various organs of Labeo rohita, Catla catla, Cirrhinus mrigala, Oreochromis mossambicus, and Cyprinus carpio cultured in sewage-fed ponds, Kolkata, India. Among the metals, cadmium, lead, and zinc were detected in water and, except lead, were below the water quality guideline levels for the protection of freshwater aquatic life proposed by CEQG (Canadian Environmental Quality Guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 10 publications
(7 reference statements)
8
26
0
2
Order By: Relevance
“…However, Pb was low compared to that of a sewage fed fish pond in East Kolkata wetland [44]. All values were within the prescribed limits for metals (Pb: 0.…”
Section: Heavy Metals In Watermentioning
confidence: 70%
“…However, Pb was low compared to that of a sewage fed fish pond in East Kolkata wetland [44]. All values were within the prescribed limits for metals (Pb: 0.…”
Section: Heavy Metals In Watermentioning
confidence: 70%
“…Worldwide, fish products represent only up to 10% of human diet; nevertheless, they represent the main uptake routes of metals (especially Hg) into the human body (Bienelli and Provini 2004;Chi et al 2007;Deshpande et al 2008;Storelli 2008;Ruelas-Inzunza et al 2010). Human health risk due to the consumption of fish loaded with metals is the subject of many recent studies (HasShön et al 2007b;Castro-Gonzales and MendezArmenta 2008;Türkmen et al 2009); furthermore, it has been shown that in some cases the intake of fish should be regulated (Chi et al 2007;Adhikari et al 2009;Nawaz et al 2009). Castro-Gonzales and Mendez-Armenta (2008) suggested not only that people should eat smaller quantities of fish known to accumulate mercury but also that they should eat a diversity of fish in order to avoid consuming unhealthy quantities of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of elements in different fish tissues depends on the function of each tissue, the uptake route, the physiology of the fish species and behavioural factors such as habitat use and feeding habits, as well as the degree of contamination (Alam et al 2002). Metals and trace elements chiefly accumulate in metabolically active tissues (Saha et al 2006, Adhikari et al 2009). The liver has been shown to be the main storage tissue for metals (Alam et al 2002, Coǧ un et al 2006, Ferreira et al 2008.…”
Section: Discussionmentioning
confidence: 99%